PELAKSANAAN PROMOSI WISATA TAMAN SATWA KANDI KOTA SAWAHLUNTO SUMATERA BARAT - Mitra Delfa; Andi M. Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this research is to know the implementation of promotion by the manager Taman Satwa Kandi and factor inhibiting in the implementation of promotion.This research used a qualitative method with descriptive approach, this subjects of this research is chairman of PT.WWS as the manager, staff of PT.WWS promotion, head of marketing and tourism cooperation department of tourism, youth and sport department, and additional informants are visitors. The data collection is made by a interview, observation, and documentation.The result of this research is manager Taman Satwa Kandi has done promotion trought four media namely advertising, sales promotion, publicity, and personal selling. The inhibiting factor of the implementation of such promotion faced by the manager is the manager is not focused on the development of a one tourist attraction only because of the management in the form of PT shelter the four attractions, the quality of existing human resources is less than optimal, and the lack of cost in promotions.Keywords : Advertising, sales promotion, publicity, personal selling